Preparation method of acid response emulsion

By combining cellulose nanocrystals with calcium carbonate, CNC/Ca nanocomposites are formed, which serves as a stabilizer for Pickering emulsions, and the problem of instability of the emulsion in an acidic environment is solved, achieving the effect of long-term stability and rapid release of the emulsion.

CN119818441AActive Publication Date: 2025-04-15ZHEJIANG WEIDING BIOTECHNOLOGY CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202510310090.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-17
Publication Date
2025-04-15
Estimated Expiration
2045-03-17

AI Technical Summary

Technical Problem

The existing Pickering emulsions are unstable in acidic environments, making it difficult to achieve the need to quickly release active substances.

Method used

By combining cellulose nanocrystals (CNC) with calcium carbonate (CaCO3), CNC/Ca nanocomposites are formed, and as a stabilizer for Pickering emulsions, electrostatic and complex interactions affect the growth and shape of CaCO3 grains to form nano-scale composite particles.

Benefits of technology

The long-term stability and acid response performance of the emulsion are achieved, the emulsion particle size is increased, the shell and three-dimensional structure are damaged, and rapid release is achieved under acidic media.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119818441A_ABST
    Figure CN119818441A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of an acid response emulsion, and relates to the technical field of emulsion preparation, the preparation method of the acid response emulsion comprises the following steps: S1, preparing volatile oil; s2, preparing CNC suspension: dispersing microcrystalline cellulose in sulfuric acid, and stirring in a water bath; carrying out dialysis treatment on the reaction product to replace redundant sulfuric acid, so as to obtain CNC (Computer Numerical Control) suspension with constant pH (Potential of Hydrogen); s3, CNC-CaCO3 composite particles are prepared; and S4, preparation of a composite emulsion: CNC influences the growth and shape of CaCO3 crystal grains through electrostatic interaction and complexation, so that nano-scale composite particles are generated, as a PE stabilizer, CNC / Ca-PE has excellent stability compared with CNC-PE and CaCO3-PE, the CNC / Ca-PE shows a PH response behavior due to participation of CaCO3 in a system, the behavior shows that the particle size of the emulsion is increased, and a shell layer and a three-dimensional structure are damaged, and the composite emulsion is prepared. And quick release under an acidic medium.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of emulsion preparation, in particular to a method for preparing an acid-responsive emulsion. Background Art

[0002] Pickering emulsion (PE) is an emulsion stabilized by solid particles instead of traditional surfactants. It has attracted much attention due to its environmental friendliness, easy preparation, and good stability. At present, PE is widely used in food packaging and biomedicine to ensure, transport and control the release of active ingredients. Take essential oil (EO) as an example. EO is a volatile aromatic oily liquid extracted from plants by water distillation. PE prepared with linden, cinnamon, citrus, and clove EO as the oil phase and cellulose, chitosan, and protein as solid particles has excellent stability, which is conducive to the protection and storage of EO active ingredients.

[0003] The main function of PE is to use solid particles to stably deliver, protect and slowly release EO components, which is a promising drug release route. Some biopolymers can form stable, pH-responsive emulsions to control active release. Specific applications require emulsions to respond to environmental stimuli to release active substances faster, such as food preservation and oral administration. The stimulus response of PE depends on the properties of solid particles and environmental factors. The particle structure and physicochemical properties give it a high-level response to environmental pH.

[0004] Responsive release systems protect active substances through core or three-dimensional structures. Cellulose and its nanoparticles are abundant biopolymers in nature and valuable stabilizers. Cellulose nanocrystals (CNCs) are needle-shaped or rod-shaped functional nanomaterials with large specific surface area, high aspect ratio, strong affinity and adsorption capacity. However, CNC has high hydrophilicity, high charge and poor emulsification properties, which hinder its adsorption at the oil-water interface and lead to unstable emulsions. At present, its emulsification ability is mainly improved by hydrophobic modification or complexation with polysaccharides and proteins. The challenge lies in managing the release of active ingredients. CNC can be chemically modified or combined with other responsive substances to not only improve the stability of the emulsion but also make its emulsion responsive.

[0005] In recent years, inorganic materials such as calcium carbonate (CaCO3) have been used to enhance the stability and stimulus responsiveness of emulsions. CaCO3, as a PE emulsifier, has attracted much attention in the food and pharmaceutical industries due to its safety, low cost, and biodegradability. Its acid responsiveness can achieve controlled targeted drug delivery, and it can also be converted into biocompatible CaCO3 under acidic conditions. 2+ , but the drug loading capacity is limited. Studies have found that CNC and Ca 2+ A small amount of Ca 2+Aggregation on the CNC surface can shield electrostatic repulsion and induce complexation and bridging. Therefore, it is assumed that combining CNC with CaCO3 can form a network structure to maintain the ultrastability of the emulsion and achieve responsive stimulation.

[0006] In this study, the applicant innovatively combined CNC with CaCO3 with responsive characteristics, successfully prepared CNC / CaCO3 (CNC / Ca) nanocomposite, and used it as a stabilizer for PE. The results of long-term stability evaluation and pH response characterization of the emulsion showed that the emulsion stabilized by CNC / Ca not only significantly enhanced its own stability, but also gave the emulsion excellent acid response performance. In short, the applicant developed a new method to enable CNC and CaCO3 to form a nanocomposite material, so that the composite material has pH response ability, and successfully applied it to maintain the long-term stability of the emulsion. Summary of the invention

[0007] In view of this, the present invention aims at the deficiencies in the prior art, and its main purpose is to provide a method for preparing an acid-responsive emulsion. CNC affects the growth and shape of CaCO3 grains through electrostatic action and complexation, thereby producing nanoscale composite particles. As a PE stabilizer, compared with CNC-PE and CaCO3-PE, CNC / Ca-PE has excellent stability. Due to the participation of CaCO3 in the system, CNC / Ca-PE exhibits pH-responsive behavior, which is manifested as an increase in the emulsion particle size, destruction of the shell and three-dimensional structure, and rapid release in an acidic medium.

[0008] To achieve the above purpose, the present invention adopts the following technical solutions: A method for preparing an acid-responsive emulsion comprises the following steps: S1, preparing volatile oil; S2. preparing a CNC suspension: dispersing microcrystalline cellulose in sulfuric acid, stirring in a water bath, and then terminating the reaction; centrifuging the reaction product to separate the precipitate; dialyzing the reaction product to displace excess sulfuric acid to obtain a CNC suspension with a constant pH; S3, preparation of CNC-CaCO3 composite particles: put Ca(OH)2 into pure water, stir at room temperature to obtain Ca(OH)2 solution; add CNC suspension, stir at room temperature to make the two mixed evenly; then introduce CO2 gas at a uniform flow rate, stir at room temperature to obtain CNC-CaCO3 composite particles; S4. Preparation of composite emulsion: using volatile oil as oil phase and CNC-CaCO3 composite particles as water phase, dropping the oil phase into the water phase containing CNC-CaCO3 composite particles, shearing, homogenizing, and obtaining a composite emulsion.

[0009] As a preferred solution: in S2, microcrystalline cellulose is dispersed in 20 times the mass fraction of 64% sulfuric acid, stirred in a water bath at 45°C and 400 rpm for 45 min, and then 10 times the amount of pure water is added to terminate the reaction; the reaction product is centrifuged at 4°C and 5000 rpm for 10 min to separate the precipitate.

[0010] As a preferred solution: in S2, the reaction product is encapsulated in a regenerated cellulose dialysis bag and dialyzed to replace excess sulfuric acid, and the CNC suspension with a constant pH is obtained by dialyzing for 5 days.

[0011] As a preferred solution: in S3, Ca(OH)2 is placed in pure water, and stirred at 500 rpm for 10 min using a magnetic stirrer at room temperature to obtain a Ca(OH)2 solution with a mass fraction of 0.07%-0.14%.

[0012] As a preferred solution: CNC suspension is added to the S3, and stirred at 500 rpm with a magnetic stirrer for 10 min at room temperature to mix the two evenly; then CO2 gas is introduced at a uniform flow rate for 10 min, and stirred at 500 rpm with a magnetic stirrer for 10-12 h at room temperature to obtain CNC-CaCO3 composite particles.

[0013] As a preferred embodiment: the volatile oil in S4 includes tea oil and Elsholtzia jiangruta volatile oil, and the specific preparation process of the Elsholtzia jiangruta volatile oil is: weigh Elsholtzia jiangruta medicinal materials, add 6-8 times of water, distill and extract for 3-5 hours, separate the water layer and the volatile oil layer, add anhydrous sodium sulfate to the volatile oil layer for dehydration, and obtain Elsholtzia jiangruta volatile oil.

[0014] As a preferred solution: the shearing in S4 is carried out at 22000 rpm for 5-10 min.

[0015] As a preferred solution: the homogenization conditions in S4 are: homogenization in a high-pressure homogenizer at a pressure of 300 bar and 500 bar for 10-30 min each.

[0016] As a preferred solution: the CNC-CaCO3 composite particles in S3 include CNC / Ca2 composite particles and CNC2 / Ca composite particles.

[0017] As a preferred embodiment: the composite emulsion in S4 includes CNC / Ca2 composite emulsion and CNC2 / Ca composite emulsion.

[0018] Compared with the prior art, the present invention has obvious advantages and beneficial effects. Specifically, it can be seen from the above technical scheme that CNC / Ca nanocomposite particles with different mass ratios are successfully prepared in this study; CNC affects the growth and shape of CaCO3 grains through electrostatic action and complexation, thereby producing nanoscale composite particles as PE stabilizers. Compared with CNC-PE and CaCO3-PE, CNC / Ca-PE has excellent stability. In addition, except for CNC1 / Ca2-PE and CNC2 / Ca3-PE, all CNC / Ca-PE remain stable for up to 4 months. Due to the participation of CaCO3 in the system, CNC / Ca-PE exhibits pH-responsive behavior, which is manifested as an increase in the particle size of the emulsion, the destruction of the shell and three-dimensional structure, and rapid release in acidic media. The EO-loaded CNC / Ca-PE nanocomposite particles exhibit good antibacterial activity, and their emulsification properties and structure affect the antibacterial activity of the composite particles. CNC / Ca-PE has a high drug loading capacity and is expected to become a pH-responsive oral drug carrier.

[0019] In order to more clearly illustrate the structural features and effects of the present invention, it is described in detail below in conjunction with the accompanying drawings and specific embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 The infrared spectra of CNC / Ca nanocomposites, CNC and CaCO3 in Examples 1 to 5 of the present invention; Figure 2 The XPS spectra of CNC / Ca nanocomposites, CNC and CaCO3 in Examples 1 to 5 of the present invention; Figure 3 This is a peak fitting high-resolution C1s spectrum of CNC in Comparative Example 1 of the present invention; Figure 4 The peak fitting high-resolution C1s spectrum of CNC1 / Ca2 in Example 1 of the present invention; Figure 5 The peak fitting high-resolution C1s spectrum of CNC2 / Ca2 in Example 2 of the present invention; Figure 6 The peak fitting high-resolution C1s spectrum of CNC3 / Ca2 in Example 3 of the present invention; Figure 7 The peak fitting high-resolution C1s spectrum of CNC2 / Ca1 in Example 4 of the present invention; Figure 8 The peak fitting high-resolution C1s spectrum of CNC2 / Ca3 in Example 5 of the present invention; Fig. 9XRD diffraction patterns of CNC / Ca nanocomposites, CNC and CaCO3 in Examples 1 to 5 of the present invention; Fig.10 This is the AFM spectrum of CNC in Comparative Example 1 of the present invention; Fig.11 This is the AFM spectrum of CaCO3 in Comparative Example 2 of the present invention; Fig.12 This is the AFM spectrum of CNC2 / Ca1 in Example 4 of the present invention; Fig.13 This is the AFM spectrum of CNC2 / Ca2 in Example 2 of the present invention; Fig.14 This is the AFM spectrum of CNC2 / Ca3 in Example 5 of the present invention; Fig.15 The elastic modulus diagram of CNC2 / Ca in Example 4, Example 2 and Example 5 of the present invention; Fig.16 TEM spectra of CNC / Ca composites and CNC and CaCO3 in Examples 1 to 5 of the present invention; Fig.17 is the TSI of CNC / Ca-PE, CNC-PE and CaCO3-PE in Examples 1 to 5 of the present invention; Fig.18 Schematic diagram of the storage time of CNC / Ca-PE, CNC-PE and CaCO3-PE in Examples 1 to 5 of the present invention; Fig.19 Microscopic images of CNC / Ca-PE, CNC-PE and CaCO3-PE at pH = 2, 7 and 12 in Examples 1 to 5 of the present invention; Fig. 20 Cryo-SEM images of CNC2 / Ca-PE and CNC-PE in Example 4, Example 2 and Example 5 of the present invention; Fig.21 Cryo-SEM images of CNC2 / Ca-PE and CNC-PE at pH=2 in Example 4, Example 2 and Example 5 of the present invention; Fig. 22 The release curves of CNC2 / Ca-PE and CNC-PE in 20% ethanol in Example 4, Example 2 and Example 5 of the present invention; Fig.23 The release curves of CNC2 / Ca-PE and CNC-PE in pH=2 HCl in Example 4, Example 2 and Example 5 of the present invention; Fig.24The release curves of CNC2 / Ca-PE and CNC-PE in pH=6.8 PBS solution in Example 4, Example 2 and Example 5 of the present invention; Fig.25 Microscopic images of CNC2 / Ca-PE and CNC-PE in Example 4, Example 2 and Example 5 of the present invention; Fig.26 The simulated gastric digestion micrographs of CNC2 / Ca-PE and CNC-PE in Examples 4, 2 and 5 of the present invention; Fig. 27 These are microscopic images of simulated intestinal digestion of CNC2 / Ca-PE and CNC-PE in Examples 4, 2 and 5 of the present invention; Fig.28 The bioaccessibility of CNC2 / Ca-PE and CNC-PE after simulated gastrointestinal digestion in Examples 4, 2 and 5 of the present invention; Fig.29 The antibacterial activity of CNC / Ca-PE and CNC-PE against Escherichia coli in Examples 1 to 5 of the present invention; Fig.30 The antibacterial activity of CNC / Ca-PE and CNC-PE in Examples 1 to 5 of the present invention against Staphylococcus aureus. DETAILED DESCRIPTION

[0021] The present invention Figure 1 As shown in FIG30 , a method for preparing an acid-responsive emulsion comprises the following steps: S1, preparing volatile oil; S2. preparing a CNC suspension: dispersing microcrystalline cellulose in sulfuric acid, stirring in a water bath, and then terminating the reaction; centrifuging the reaction product to separate the precipitate; dialyzing the reaction product to displace excess sulfuric acid to obtain a CNC suspension with a constant pH; S3, preparation of CNC-CaCO3 composite particles: put Ca(OH)2 into pure water, stir at room temperature to obtain Ca(OH)2 solution; add CNC suspension, stir at room temperature to make the two mixed evenly; then introduce CO2 gas at a uniform flow rate, stir at room temperature to obtain CNC-CaCO3 composite particles; S4. Preparation of composite emulsion: using volatile oil as oil phase and CNC-CaCO3 composite particles as water phase, dropping the oil phase into the water phase containing CNC-CaCO3 composite particles, shearing, homogenizing, and obtaining a composite emulsion.

[0022] In S2, microcrystalline cellulose is dispersed in 20 times the mass fraction of 64% sulfuric acid, stirred in a water bath at 45°C and 400 rpm for 45 min, and then 10 times the mass fraction of pure water is added to terminate the reaction; the reaction product is centrifuged at 4°C and 5000 rpm for 10 min to separate the precipitate.

[0023] In S2, the reaction product is encapsulated in a regenerated cellulose dialysis bag and dialyzed to replace excess sulfuric acid. The CNC suspension with a constant pH is obtained by dialyzing for 5 days.

[0024] In S3, Ca(OH)2 is placed in pure water, and stirred at room temperature using a magnetic stirrer at 500 rpm for 10 min to obtain a Ca(OH)2 solution with a mass fraction of 0.07%-0.14%.

[0025] The CNC suspension was added to the S3, and stirred at 500 rpm with a magnetic stirrer for 10 min at room temperature to make the two mixed evenly; then, CO2 gas was introduced at a uniform flow rate for 10 min, and stirred at 500 rpm with a magnetic stirrer for 10-12 h at room temperature to obtain CNC-CaCO3 composite particles.

[0026] The volatile oil in S4 includes tea oil and Elsholtzia jiangruta volatile oil. The specific preparation process of the Elsholtzia jiangruta volatile oil is as follows: weigh Elsholtzia jiangruta medicinal materials, add 6-8 times of water, distill and extract for 3-5 hours, separate the water layer and the volatile oil layer, add anhydrous sodium sulfate to the volatile oil layer for dehydration, and obtain the Elsholtzia jiangruta volatile oil.

[0027] The S4 was sheared at 22,000 rpm for 5-10 min.

[0028] The homogenization conditions in S4 are: homogenization in a high-pressure homogenizer at a pressure of 300 bar and 500 bar for 10-30 minutes respectively.

[0029] The CNC-CaCO3 composite particles in S3 include CNC / Ca2 composite particles and CNC2 / Ca composite particles.

[0030] The composite emulsion in S4 includes CNC / Ca2 composite emulsion and CNC2 / Ca composite emulsion.

[0031] Example 1: A method for preparing an acid-responsive emulsion, comprising the following steps: S1. Weigh the medicinal material of Elsholtzia jiangruta, put it into a round-bottom flask, add 6 times the amount of water, distill and extract for 3 hours, stop heating, open the valve, separate the water layer and the volatile oil layer, add anhydrous sodium sulfate to the volatile oil layer for dehydration, and obtain Elsholtzia jiangruta volatile oil.

[0032] S2. Prepare CNC suspension. Disperse MCC in 20 times (m / v) 64 wt% sulfuric acid. Stir in a water bath at 45 °C and 400 rpm for 45 min. Then add 10 times pure water to terminate the reaction. The reaction product is centrifuged at 4 °C and 5000 rpm for 10 min. The reaction product is encapsulated in a regenerated cellulose dialysis bag (12,000 Kda) for dialysis to replace excess acid. Dialysis for 5 days to obtain a CNC suspension with a constant pH. Dilute the CNC suspension to 0.4% (m / v).

[0033] Preparation of S3 and CNC1 / Ca2 composite particles: 0.0700g of Ca(OH)2 was added to 55.22mL of pure water. At room temperature, a magnetic stirrer was used to stir at 500 rpm for 10 min to obtain a 0.1% Ca(OH)2 solution. 14.78 mL of the 0.4% CNC suspension prepared in S2 was taken to make the volume of the two 70 mL. At room temperature, a magnetic stirrer was used to stir at 500 rpm for 10 min to mix the two evenly. Then, CO2 gas was introduced at a uniform flow rate for 10 min. At room temperature, a magnetic stirrer was used to stir at 500 rpm overnight to obtain a CNC1 / Ca2 complex.

[0034] S4, preparation of emulsion, 16.8 mL tea oil and 4.2 mL Elsholtzia elata volatile oil were mixed evenly as the oil phase, and 49 mL of CNC1 / Ca2 complex prepared in S3 was taken as the water phase. The oil phase was slowly dripped into the water phase containing the CNC1 / Ca2 complex, sheared at 22000 rpm for 5 min, and then transferred to a high-pressure homogenizer at a pressure of 300 bar and 500 bar for homogenization for 21 min each, to obtain an emulsion stabilized by the CNC1 / Ca2 complex.

[0035] Example 2: A method for preparing an acid-responsive emulsion, comprising the following steps: S1. Weigh the medicinal material of Elsholtzia jiangruta, put it into a round-bottom flask, add 6 times the amount of water, distill and extract for 3 hours, stop heating, open the valve, separate the water layer and the volatile oil layer, add anhydrous sodium sulfate to the volatile oil layer for dehydration, and obtain Elsholtzia jiangruta volatile oil.

[0036] S2. Prepare CNC suspension. Disperse MCC in 20 times (m / v) 64 wt% sulfuric acid. Stir in a water bath at 45 °C and 400 rpm for 45 min. Then add 10 times pure water to terminate the reaction. The reaction product is centrifuged at 4 °C and 5000 rpm for 10 min. The reaction product is encapsulated in a regenerated cellulose dialysis bag (12,000 Kda) for dialysis to replace excess acid. Dialysis for 5 days to obtain a CNC suspension with a constant pH. Dilute the CNC suspension to 0.7% (m / v).

[0037] Preparation of S3 and CNC2 / Ca2 composite particles: 0.0705 g of Ca(OH)2 was added to 45.37 mL of pure water. At room temperature, a magnetic stirrer was used to stir at 500 rpm for 10 min to obtain a 0.1% Ca(OH)2 solution. 24.63 mL of the 0.7% CNC suspension prepared in S2 was taken to make the volume of the two 70 mL. At room temperature, a magnetic stirrer was used to stir at 500 rpm for 10 min to mix the two evenly. Then, CO2 gas was introduced at a uniform flow rate for 10 min. At room temperature, a magnetic stirrer was used to stir at 500 rpm overnight to obtain a CNC2 / Ca2 complex.

[0038] S4, preparation of emulsion, 16.8 mL tea oil and 4.2 mL Elsholtzia elata volatile oil were mixed evenly as the oil phase, and 49 mL of CNC2 / Ca2 complex prepared in S3 was taken as the water phase. The oil phase was slowly dripped into the water phase containing the CNC2 / Ca2 complex, sheared at 22000 rpm for 5 min, and then transferred to a high-pressure homogenizer at a pressure of 300 bar and 500 bar for homogenization for 21 min each, to obtain a stable emulsion of CNC2 / Ca2 complex.

[0039] Example 3: A method for preparing an acid-responsive emulsion, comprising the following steps: S1. Weigh the medicinal material of Elsholtzia jiangruta, put it into a round-bottom flask, add 6 times the amount of water, distill and extract for 3 hours, stop heating, open the valve, separate the water layer and the volatile oil layer, add anhydrous sodium sulfate to the volatile oil layer for dehydration, and obtain Elsholtzia jiangruta volatile oil.

[0040] S2. Prepare CNC suspension. Disperse MCC in 20 times (mass / volume) of 64 wt% sulfuric acid. Stir in a water bath at 45 °C and 400 rpm for 45 min. Then add 10 times of pure water to terminate the reaction. The reaction product is centrifuged at 4 °C and 5000 rpm for 10 min. The reaction product is encapsulated in a regenerated cellulose dialysis bag (12,000 Kda) for dialysis to replace excess acid. Dialysis for 5 days to obtain a CNC suspension with a constant pH. Dilute the CNC suspension to 1% (m / v).

[0041] Preparation of S3 and CNC3 / Ca2 composite particles: 0.0705 g of Ca(OH)2 was added to 35.52 mL of pure water. At room temperature, a magnetic stirrer was used to stir at 500 rpm for 10 min to obtain a 0.1% Ca(OH)2 solution. 34.48 mL of the 1% CNC suspension prepared by S2 was taken to make the volume of the two 70 mL. At room temperature, a magnetic stirrer was used to stir at 500 rpm for 10 min to mix the two evenly. Then, CO2 gas was introduced at a uniform flow rate for 10 min. At room temperature, a magnetic stirrer was used to stir at 500 rpm overnight to obtain a CNC3 / Ca2 complex.

[0042] S4, preparation of emulsion, 16.8 mL tea oil and 4.2 mL Elsholtzia elata volatile oil were mixed evenly as the oil phase, and 49 mL of CNC3 / Ca2 complex prepared in S3 was taken as the water phase. The oil phase was slowly dripped into the water phase containing the CNC3 / Ca2 complex, sheared at 22000 rpm for 5 min, and then transferred to a high-pressure homogenizer at a pressure of 300 bar and 500 bar for homogenization for 21 min each, to obtain a stable emulsion of CNC3 / Ca2 complex.

[0043] Example 4: A method for preparing an acid-responsive emulsion, comprising the following steps: S1. Weigh the medicinal material of Elsholtzia jiangruta, put it into a round-bottom flask, add 6 times the amount of water, distill and extract for 3 hours, stop heating, open the valve, separate the water layer and the volatile oil layer, add anhydrous sodium sulfate to the volatile oil layer for dehydration, and obtain Elsholtzia jiangruta volatile oil.

[0044] S2. Prepare CNC suspension. Disperse MCC in 20 times (m / v) 64 wt% sulfuric acid. Stir in a water bath at 45 °C and 400 rpm for 45 min. Then add 10 times pure water to terminate the reaction. The reaction product is centrifuged at 4 °C and 5000 rpm for 10 min. The reaction product is encapsulated in a regenerated cellulose dialysis bag (12,000 Kda) for dialysis to replace excess acid. Dialysis for 5 days to obtain a CNC suspension with a constant pH. Dilute the CNC suspension to 0.7% (m / v).

[0045] Preparation of S3 and CNC2 / Ca1 composite particles: 0.0507 g of Ca(OH)2 was added to 45.37 mL of pure water. At room temperature, a magnetic stirrer was used to stir for 10 min at 500 rpm to obtain a 0.07% Ca(OH)2 solution. 24.63 mL of the 0.7% CNC suspension prepared in S2 was taken to make the volume of the two 70 mL. At room temperature, a magnetic stirrer was used to stir for 10 min at 500 rpm to mix the two evenly. Then, CO2 gas was introduced at a uniform flow rate for 10 min. At room temperature, a magnetic stirrer was used to stir overnight at 500 rpm to obtain a CNC2 / Ca1 complex.

[0046] S4, preparation of emulsion, 16.8 mL tea oil and 4.2 mL Elsholtzia elata volatile oil were mixed evenly as the oil phase, and 49 mL of CNC2 / Ca1 complex prepared in S3 was taken as the water phase. The oil phase was slowly dripped into the water phase containing the CNC2 / Ca1 complex, sheared at 22000 rpm for 5 min, and then transferred to a high-pressure homogenizer at a pressure of 300 bar and 500 bar for homogenization for 21 min each, to obtain a stable emulsion of CNC2 / Ca1 complex.

[0047] Example 5: A method for preparing an acid-responsive emulsion, comprising the following steps: S1. Weigh the medicinal material of Elsholtzia jiangruta, put it into a round-bottom flask, add 6 times the amount of water, distill and extract for 3 hours, stop heating, open the valve, separate the water layer and the volatile oil layer, add anhydrous sodium sulfate to the volatile oil layer for dehydration, and obtain Elsholtzia jiangruta volatile oil.

[0048] S2. Prepare CNC suspension. Disperse MCC in 20 times (m / v) 64 wt% sulfuric acid. Stir in a water bath at 45 °C and 400 rpm for 45 min. Then add 10 times pure water to terminate the reaction. The reaction product is centrifuged at 4 °C and 5000 rpm for 10 min. The reaction product is encapsulated in a regenerated cellulose dialysis bag (12,000 Kda) for dialysis to replace excess acid. Dialysis for 5 days to obtain a CNC suspension with a constant pH. Dilute the CNC suspension to 0.7% (m / v).

[0049] Preparation of S3 and CNC2 / Ca3 composite particles: 0.1001 g of Ca(OH)2 was added to 45.37 mL of pure water. At room temperature, a magnetic stirrer was used to stir at 500 rpm for 10 min to obtain a 0.14% Ca(OH)2 solution. 24.63 mL of the 0.7% CNC suspension prepared by S2 was taken to make the volume of the two 70 mL. At room temperature, a magnetic stirrer was used to stir at 500 rpm for 10 min to mix the two evenly. Then, CO2 gas was introduced at a uniform flow rate for 10 min. At room temperature, a magnetic stirrer was used to stir at 500 rpm overnight to obtain a CNC2 / Ca3 complex.

[0050] S4, preparation of emulsion, 16.8 mL tea oil and 4.2 mL Elsholtzia elata volatile oil were mixed evenly as the oil phase, and 49 mL of CNC2 / Ca3 complex prepared in S3 was taken as the water phase. The oil phase was slowly dripped into the water phase containing the CNC2 / Ca3 complex, sheared at 22000 rpm for 5 min, and then transferred to a high-pressure homogenizer at a pressure of 300 bar and 500 bar for homogenization for 21 min each, to obtain an emulsion stabilized by the CNC2 / Ca3 complex.

[0051] Comparative Example 1: A method for preparing a CNC emulsion without adding CaCO3, comprising the following steps: S1. Weigh the medicinal material of Elsholtzia jiangruta, put it into a round-bottom flask, add 6 times the amount of water, distill and extract for 3 hours, stop heating, open the valve, separate the water layer and the volatile oil layer, add anhydrous sodium sulfate to the volatile oil layer for dehydration, and obtain Elsholtzia jiangruta volatile oil.

[0052] S2. Prepare 0.7% CNC suspension, disperse MCC in 20 times (m / v) 64 wt% sulfuric acid, stir in a water bath at 45 °C and 400 rpm for 45 min, then add 10 times pure water to terminate the reaction. The reaction product is centrifuged at 4 °C and 5000 rpm for 10 min, and the reaction product is encapsulated in a regenerated cellulose dialysis bag (12,000 Kda) for dialysis to replace excess acid. Dialysis for 5 days to obtain a CNC suspension with a constant pH. Dilute the CNC suspension to 0.7% (m / v).

[0053] S3, prepare CNC emulsion, take 16.8 mL and 4.2 mL of Elsholtzia radiata volatile oil, mix them evenly as the oil phase, take 49 mL of CNC suspension prepared in S2 as the water phase. Slowly drip the oil phase into the CNC suspension, shear at 22000 rpm for 5 min, and then transfer it to a high-pressure homogenizer at a pressure of 300 bar and 500 bar for homogenization for 21 min each, to obtain a CNC stable emulsion.

[0054] Comparative Example 2: A method for preparing a CaCO3 emulsion without adding CNC, comprising the following steps: S1. Weigh the medicinal material of Elsholtzia jiangruta, put it into a round-bottom flask, add 6 times the amount of water, distill and extract for 3 hours, stop heating, open the valve, separate the water layer and the volatile oil layer, add anhydrous sodium sulfate to the volatile oil layer for dehydration, and obtain Elsholtzia jiangruta volatile oil.

[0055] S2. Preparation of CaCO3 particles: add 0.1001 g of Ca(OH)2 to 70 mL of pure water, stir at room temperature with a magnetic stirrer at 500 rpm for 10 min to obtain a 0.1% Ca(OH)2 solution, then introduce CO2 gas at a uniform flow rate for 10 min, and complete the reaction with a magnetic stirrer at 500 rpm at room temperature to obtain CaCO3 particles.

[0056] S3, prepare CaCO3 emulsion, take 16.8 mL tea oil and 4.2 mL Elsholtzia elata volatile oil, mix them evenly as the oil phase, take 49 mL of the CaCO3 suspension prepared in S2 as the water phase. Slowly drip the oil phase into the CaCO3 suspension, shear at 22000 rpm for 5 min, and then transfer it to a high-pressure homogenizer at a pressure of 300 bar and 500 bar for homogenization for 21 min each, to obtain a CaCO3 stable emulsion.

[0057] Test Example 1: Determination of composite infrared: The CNC / Ca nanocomposites, CNC and CaCO3 prepared in Examples 1 to 5 were mixed with potassium bromide and pressed into tablets respectively for infrared spectroscopy analysis using a Fourier transform infrared spectrometer at a wavelength of 4000-400 cm-1, a resolution of 4 cm-1, and a cumulative number of scans of 16. The ratio of potassium bromide to sample was 100:1 (mg / mg). The infrared spectra of CNC1 / Ca2, CNC2 / Ca2, CNC3 / Ca2, CNC2 / Ca1, CNC2 / Ca3 and CNC and CaCO3 in Examples 1 to 5 were measured, and the results are shown in FIG. Figure 1 .

[0058] Result analysis: Figure 1 It can be seen that the CNC / Ca nanocomposites in Examples 1 to 5 retain the original peaks of CNC and CaCO3. The characteristic peak position of CNC is 3338 cm -1 and 2902 cm -1 , which is attributed to the -OH and CH stretching vibrations in the cellulose molecules. The CaCO3 particles have a peak at 1424 cm -1 、875 cm -1 and 713 cm -1There is an absorption peak at 1424 cm -1 The V3 characteristic absorption peak at 875 cm is the antisymmetric stretching vibration of CO. -1 It is the V2 absorption peak of CaCO3 calcite crystal and CO3 2- Out-of-plane deformation vibration peak. 713 cm -1 is the V4 absorption peak of calcite CaCO3 crystals, which is related to the bending vibration of CO bonds. Therefore, the CaCO3 particles produced in this study are calcite crystals. In the FT-IR spectra of CNC / Ca nanocomposite particles, due to the relatively high content of CaCO3 in the nanocomposite particles, CNC1 / Ca2, CNC2 / Ca2 and CNC2 / Ca3 have a peak at 875 cm -1 When the CNC / Ca nanocomposite particles in Examples 1 to 5 were prepared, the characteristic peaks of the single components were retained, indicating that the process of preparing the obtained CNC / Ca nanocomposite with different ratios of CNC and CaCO3 is a physical process.

[0059] Test Example 2: X-ray Photoelectron Spectroscopy Analysis The CNC / Ca nanocomposites, CNC and CaCO3 prepared in Examples 1 to 5 were measured using an XPS spectrometer. The XPS spectra of C, O and Ca atoms on the sample surface were obtained using Avantage software under the conditions of 12 kV, Al Kα irradiation (hv=1486.6 eV), beam spot 400 μm, pass energy 50 eV and step size 0.1 eV. The XPS spectra of CNC1 / Ca2, CNC2 / Ca2, CNC3 / Ca2, CNC2 / Ca1, CNC2 / Ca3 and CNC and CaCO3 in Examples 1 to 5 were measured, and the results are shown in Table 1. Figure 2-Figure 8 and Table 1.

[0060] Table 1: Atomic density of CNC / Ca nanocomposites, CNC and CaCO3 in Examples 1 to 5

[0061] Result analysis: Figure 2 It can be seen that the XPS spectrum of CNC shows characteristic peaks of carbon (C) and oxygen (O). The C peak appears at 284-286 eV, and the O peak appears at 531-532 eV, which are mainly related to hydroxyl (-OH), aldehyde (-CHO) and carboxyl (-COOH). + and CO3² -The XPS shows characteristic peaks corresponding to carbon (C), oxygen (C), and calcium (Ca). The CNC / Ca nanocomposite particles show typical peaks of C1, Ca2p, and O1 at about 286 eV, 347-348 eV, and 533 eV, respectively. The atomic density of CNC, CaCO3, and CNC / Ca nanocomposite particles is shown in Table 1. CNC is composed of D-glucose units (C6H 10 O5)n, and shows high density of C (57.44%) and O (42.56%) signals. The C element accounts for 40.40% of the CaCO3 particles, which is caused by the background noise generated by the carbon support film of the copper grid, so the C signal can be ignored. The relative density of atoms is related to the relative content of elements on the surface of the composite particles. Due to the low relative content of CaCO3, the Ca atomic density of CNC2 / Ca1 and CNC3 / Ca2 nanocomposites is 0.69% and 0.79%, respectively. The relative content of CaCO3 in CNC2 / Ca3 nanocomposites is the highest, but the relative content of elemental Ca is low (0.71%). This may be due to the fact that most of the CaCO3 is wrapped by CNC, resulting in only a small amount of Ca element being detected on the surface of the material. XPS analysis can also determine the nature of the bonds involved in the surface of the material by deconvolution. In this work, C1s in CNC and CNC / Ca nanocomposite particles were deconvoluted, and the results are shown in Figure 2. Figure 3-Figure 8 The C1s peak is decomposed into three peaks: COC, CC, and OC=O, indicating that there is a non-covalent interaction between the surface groups of CNC and CaCO3.

[0062] Test Example 3: X-ray diffraction measurement: The CNC / Ca nanocomposites and CNC and CaCO3 in different ratios in Examples 1 to 5 were characterized by diffraction using Cu Kα radiation under the conditions of a current of 40 mA, a voltage of 40 kV, a scanning speed of 2° / min, and a scanning range of 10°-80°. The XRD spectra of CNC1 / Ca2, CNC2 / Ca2, CNC3 / Ca2, CNC2 / Ca1, CNC2 / Ca3, and CNC and CaCO3 in Examples 1 to 5 were measured, and the results are shown in FIG. Fig. 9 .

[0063] Result analysis: Fig. 9It can be seen that all CNC / Ca nanocomposite particles retain the diffraction peaks of CNC. CNC has obvious characteristic peaks near 14.8°, 16.6°, 22.7° and 34.5°, which correspond to the crystal planes (1-10), (110), (200) and (004) of cellulose Iβ, respectively. A typical calcite polycrystalline peak was found at 29.3° in the XRD spectrum of CaCO3. In addition, the characteristic peaks of CaCO3 at 23.05°, 29.39°, 35.98°, 39.42°, 43.16°, 47.5°, 48.50° and 57.40° correspond to Ca. In CNC / Ca nanocomposite particles with different ratios, as the relative content of CNC decreases, the diffraction peaks of cellulose type I crystal structure at 16.0° and 22.0° decrease. This phenomenon is attributed to the increase in the proportion of composite particles in the crystalline region and amorphous region in the amorphous structure of CaCO3. In addition, the diffraction peaks of CaCO3 appeared in the XRD patterns of all CNC / Ca nanocomposite particles, but the intensity of the crystallization peak of CaCO3 particles decreased, which may be due to the effect of CNC on the growth and crystallization transformation of CaCO3 particles.

[0064] Test Example 4: Composite AFM measurement: Using a high-resolution scanning probe microscope (AFM), the CNC2 / Ca composites prepared in different mass ratios in Example 4, Example 2 and Example 5 and the CNC and CaCO3 suspensions were dropped onto a mica sheet and dried naturally at 25°C for two hours. The apparent morphology and elastic modulus of the particles were observed by the capture mode. The AFM images of CNC2 / Ca1, CNC2 / Ca2, CNC2 / Ca3, CNC and CaCO3 in Example 4, Example 2 and Example 5 were measured. The results are shown in FIG. Figure 10-Figure 15 .

[0065] Result analysis: Figure 10-Figure 14 It can be seen that the surface roughness of CNC and CaCO3 is 2.60 nm and 3.26 nm, respectively. The surface roughness of CNC2 / Ca1, CNC2 / Ca2 and CNC2 / Ca3 are 4.41, 4.55 and 5.27 nm, respectively, indicating that the surface roughness of the nanocomposite particles formed by different masses of CaCO3 and CNC is significantly enhanced. With the increase of CaCO3 content, the surface roughness of CNC / Ca nanocomposites gradually increases. The rough surface provides a larger surface area to enhance adsorption at the oil-water interface, which helps to maintain the stability of the emulsion. Fig.15It can be seen that the elastic modulus of CNC and CaCO3 of CNC, CaCO3 and CNC2 / Ca nanocomposite particles are (5.34±0.1) GPa and (6.68±0.11) GPa, respectively. CNC and CaCO3 are both high rigidity materials. The elastic moduli of CNC2 / Ca1, CNC2 / Ca2 and CNC2 / Ca3 are (4.93±0.38), (4.06±0.24) and (3.33±0.17) GPa, respectively. The smaller the elastic modulus, the stronger the deformation ability. The significant deformability of the particles can give them additional degrees of freedom at the interface to cover a larger interface area, resist extrusion and increase adsorption capacity. The nanocomposite particles have a smaller elastic modulus, indicating that it is easier to form a three-dimensional lattice structure under high-pressure homogenization conditions.

[0066] Test Example 5: TEM determination of composites: Using transmission electron microscopy, the CNC / Ca composites of different mass ratios prepared in Examples 1 to 5 and the suspensions of CNC and CaCO3 were precipitated on a Cu grid and stained with uranyl acetate. The samples were dried naturally at room temperature and then imaged using an electron microscope at an accelerating voltage of 80-120 kV. The TEM images of CNC1 / Ca2, CNC2 / Ca2, CNC3 / Ca2, CNC2 / Ca1, CNC2 / Ca3, CNC and CaCO3 in Examples 1 to 5 were measured, and the results are shown in FIG. Fig.16 .

[0067] Result analysis: Fig.16 It can be seen that CNC is a nanoscale needle-like structure. Due to the removal of non-crystalline areas, the CaCO3 particles are of a square crystal structure, which is consistent with the FT-IR and XRD results. In the TEM image of CNC / Ca nanocomposite particles, the square CaCO3 does not appear in the field of view, but is replaced by a round CaCO3 crystal nucleus. Although CNC does not affect the nucleation of CaCO3, it affects the growth and structure of CaCO3 grains, which is consistent with the XRD results. 2+ Due to the electrostatic adsorption effect, CNC is easily adsorbed onto the primary nuclei of CaCO3, resulting in the inhibition of the growth of CaCO3 grains into smooth spherical or irregular surface nanoscale primary grains. 2+ The strong complexation between the nanoparticles leads to the formation of smooth spherical CaCO3 particles of about 300 nm in the system, and CNC is adsorbed around the surface of the CaCO3 particles. The spherical CaCO3 in the nanoparticles can be arranged relatively tightly in oil and water to form a more stable interfacial film, which is beneficial to the stability of the emulsion. The morphology of CaCO3 in the CNC2 / Ca3 system is inconsistent with other samples. CNC is entangled on the surface of CaCO3 particles, which is consistent with the XPS results. This may be due to the higher concentration of Ca in the system.2+ The interaction on the CNC surface formed CaCO3 crystallites instead of CaCO3 particles, resulting in irregular shape and larger size of CaCO3 particles.

[0068] Test Example 6: Emulsion Long-term Stability Analysis The stability of the emulsions was recorded using a Turbiscan laboratory stability analyzer. About 20 mL of the freshly prepared emulsion was placed in a bottle and scanned from bottom to top every 10 min for 1 day at 25 °C to record the Turbiscan stability index (TSI). Fresh CNC-PE and CNC / Ca-PE were stored at room temperature for 0, 15, 30, 60, 90, and 120 days, and the changes in the appearance of the emulsions were photographed to evaluate the long-term stability of the emulsions. The results are shown in Fig.17 and Fig.18 .

[0069] Result analysis: Fig.17 It can be seen that in Comparative Example 1, the TSI of CNC-PE increased rapidly within 5 h, indicating that a single CNC is not enough to improve the stability of the emulsion. In Comparative Example 2, the TSI value of CaCO3-PE showed an upward trend within 24 h. Adding a small amount of CaCO3 can effectively improve the stability of CNC-PE, reduce the TSI of the emulsion, and effectively slow down the migration speed of the emulsion droplets. Adjusting the ratio of CNC to CaCO3 further enhances the stability.

[0070] The results are as follows Fig.18 It can be seen that in Comparative Example 1, CNC-PE exhibited weak emulsification and emulsification stability, which is due to the weak interfacial adsorption of CNC in the continuous phase and the strong electrostatic repulsion. The protection ability of CaCO3 particles to EO is weak, so the newly prepared Comparative Example 2 shows oil phase separation. During the storage period of 30 days, CaCO3-PE showed stratification. Due to the excessive initial particle size of CaCO3 or the weak adsorption energy on the oil-water interface, the surface of the emulsion droplets formed after homogenization cannot be stably adsorbed. In Examples 1 to 5, when CNC is combined with CaCO3, the emulsification ability of CNC / Ca nanocomposite particles and the long-term stability of the stabilized emulsion are significantly improved. CNC1 / Ca2-PE and CNC2 / Ca3-PE show obvious oil phase exudation with the extension of storage time. However, CNC2 / Ca2-PE, CNC3 / Ca2-PE and CNC2 / Ca1-PE did not show stratification and oil phase exudation during long-term storage (120 days) at room temperature, which may be due to the complexation of CNC with a certain mass ratio of Ca ions, which enhanced the fixation of the interface layer. The appropriate nanocomposite particle size is conducive to the enhanced construction of the three-dimensional network in the continuous phase of the emulsion.

[0071] Test Example 7: Emulsion pH Responsiveness The structural behavior of CNC and CNC / Ca-PE under different pH environments was observed, and the pH responsiveness of the emulsions was investigated. The pH of CNC and CNC / Ca-PE was adjusted to 2, 7, and 12 using 0.1 mol / L HCl and NaOH solutions. After being stored at room temperature for 24 h, the microscopic morphology of the emulsions was recorded using a DS-Fi2 microscope equipped with NIS elements. The results are shown in Fig.19 .

[0072] Freshly prepared and pH=2 treated CNC2 / Ca1-PE, CNC2 / Ca2-PE and CNC2 / Ca3-PE in Example 4, Example 2 and Example 5 and Comparative Example 1 CNC-PE were observed using Cryo-SEM. Briefly, the emulsion samples were flash frozen in liquid nitrogen at -140°C for 30 s. The frozen samples were transferred to the preparation chamber by a cryotransfer system (Quorum PP3000T, UK) and sublimated gold coating was performed under vacuum. The apparent morphology of the emulsion was observed at -90°C and imaged at 15,000X. The results are shown in Fig. 20 and Fig.21 .

[0073] Result analysis: Fig.19 It can be seen that at pH = 7 and pH = 12, the droplets of CNC / Ca-PE, CNC-PE and CaCO3-PE in Examples 1 to 5 are very small. This may be due to the fact that CNC / Ca-PE, CNC-PE and CaCO3-PE have strong electrostatic and spatial repulsion under neutral and alkaline conditions, which effectively prevents the aggregation of emulsion droplets. Under acidic conditions (pH = 2), due to the weak stability of Comparative Example 1, some weak droplets have a slight increase trend, resulting in flocculation of some weak droplets. Under acidic conditions, the microstructure of the emulsion stabilized by CNC / Ca nanocomposite particles in Comparative Example 2 and Examples 1 to 5 shows different changes. Due to the disintegration of the CaCO3 particles on the surface of the emulsified droplets, the oil phase is completely exposed to the water phase, and the emulsion droplets in Comparative Example 2 almost disappear, indicating that CaCO3-PE has a strong acid response behavior. In the acidic environment of CNC / Ca-PE in Examples 1 to 5, the CaCO3 particles on the surface of the droplets disappeared, resulting in thinning of the interface film or cavities, and the droplets obviously aggregated and increased in size. This result shows that CNC / Ca-PE has a certain responsiveness, and this behavior is attributed to the effect of pH on CaCO3 particles.

[0074] In order to further explore the effect of acidic environment on the structure of CNC / Ca-PE emulsion droplets, Cryo-SEM was used to observe the interface details of emulsion droplets at pH=2 to reveal the acid response behavior mechanism of the emulsion. Fig. 20It can be seen that the surface of the droplets of all emulsion samples before acid treatment is wrapped by a dense interface layer responsible for maintaining and stabilizing the emulsion. In Comparative Example 1, obvious fiber structure decoration can be seen on the surface of the spherical CNC-PE droplets. In Example 4 and Example 2, there are disordered chain connections between the tiny droplets of CNC2 / Ca1-PE and CNC2 / Ca2-PE. This may be due to the fact that a large amount of CNC and Ca2-PE 2+ Complexation forms a chain network. This chain network plays an important role in limiting droplet migration and preventing droplet aggregation. In Example 5, the droplets of CNC2 / Ca3-PE are larger and there is no network connection between the droplets. This is because the CNC2 / Ca3 nanocomposite particles are adsorbed on the surface of the oil droplets, limiting the contact with the particles in the system, resulting in insufficient attraction to form a network.

[0075] After acid treatment, the surface structural features of the emulsion droplets are Fig.21 It can be seen that. In Comparative Example 1, the surface of the CNC-PE droplet lost the adsorbed cellulose structure, but the interfacial film structure was intact and the droplet size did not change significantly. In Example 4, Example 2 and Example 5, after the CNC / Ca-PE was treated with acid, the droplet size increased and the droplet surface was broken. Among them, CNC2 / Ca1-PE and CNC2 / Ca2-PE showed droplet aggregation, larger droplets, droplet breakage and disappearance of the network structure. This is because there is no CaCO3 in the emulsion system under acidic conditions, which leads to the weakening of the interfacial film and network structure in the emulsion. The droplet size of CNC2 / Ca3-PE does not change significantly, and only slight fractures appear on the droplet surface, which is related to the structure of the CNC2 / Ca3 nanocomposite. For CNC2 / Ca3 nanocomposite particles, CNC is tightly wrapped around the CaCO3 particles to prevent the attack of hydrochloric acid, resulting in only some CaCO3 particles not being covered by CNC and damaged by acid.

[0076] Test Example 8: Emulsion in vitro release The in vitro release characteristics of CNC / Ca-PE were determined by dialysis. The CNC2 / Ca1, CNC2 / Ca2 and CNC2 / Ca3 nanocomposites in Examples 4, 2 and 5 and the CNC-stabilized emulsions in Comparative Example 1 were used to determine the emulsion release. Briefly, 0.2 mL of the emulsion was placed in a dialysis bag (0.5-1 kDa), rotated at 200 rpm at 37 °C, and incubated in 20% ethanol (containing 0.1% Tween 80), 0.1 mL HCl (containing 0.1% Tween 80) and pH=6.8 PBS buffer (containing 0.1% Tween 80), respectively. At 0, 0.25, 0.5, 1, 2, 4, 6, 8, 10, and 12 h, 3 mL of sample was taken from the culture medium and replaced with 3 mL of preheated culture medium. The EO content in the culture medium at different time points of the culture was determined at 277 nm using a Shimadzu UV-2600 spectrophotometer. The cumulative release percentage of EO was calculated and all samples were analyzed three times. The results are shown in Figure 22-Figure 24 .

[0077] Results from Figure 22-Figure 24 It can be seen that in the ethanol medium, the cumulative release rate of CNC-PE in Comparative Example 1 is 71.47±0.77%, while in Example 4, Example 2 and Example 5, the cumulative release rates of CNC2 / Ca1-PE, CNC2 / Ca2-PE and CNC2 / Ca3-PE are 70.82±4.25%, 63.71±2.97% and 69.62±2.59%, respectively. Comparative Example 1 shows a faster release rate, while in Examples 1 to 5, the CNC / Ca nanocomposite stable emulsion slows down the release of EO from the emulsion to varying degrees in the alcohol medium. Therefore, the CNC / Ca nanocomposite particles improve the stability of the emulsion and make the emulsion release slower in the alcohol medium. This slow release rate may help reduce the drug leakage of EO during blood circulation.

[0078] In acidic medium, the cumulative release rate of CNC-PE in Comparative Example 1 is 51.51±11.31%, while in Examples 4, 2 and 5, the cumulative release rates of CNC2 / Ca1-PE, CNC2 / Ca2-PE and CNC2 / Ca3-PE are 60.16±5.49%, 61.39±1.30% and 62.81±2.38%, respectively. The emulsions stabilized by CNC / Ca nanocomposite particles in Examples 4, 2 and 5 have a faster release rate than the CNC-PE in Comparative Example 1, which is caused by the demulsification effect of the CNC / Ca-PE emulsion under the stimulation of an acidic environment. In pH = 6.8 PBS buffer, the cumulative release rate of CNC-PE in Comparative Example 1 was 56.16 ± 2.46%, while in Example 4, Example 2 and Example 5, the cumulative release rates of CNC2 / Ca1-PE, CNC2 / Ca2-PE and CNC2 / Ca3-PE were 53.37 ± 1.90%, 46.48 ± 1.09% and 49.87 ± 3.66%, respectively. The in vitro release results showed that compared with ethanol and acidic media, CNC / Ca-PE released less EO in pH = 6.8 PBS buffer.

[0079] Test Example 9: Emulsion simulated gastrointestinal release A simulated gastrointestinal digestion system was constructed to study the potential gastrointestinal digestion fate of EO delivery samples (CNC2 / Ca1-PE, CNC2 / Ca2-PE, CNC2 / Ca3-PE and CNC-PE in Examples 4, 2 and 5). The emulsion samples were digested in simulated gastric fluid (SGF) and simulated intestinal fluid (SIF) in turn. Simulated gastric digestion: The emulsion was mixed with SGF at a ratio of 1:1 (v / v), the pH was adjusted to 2 with 0.1 mL of HCl solution, and then incubated at 37 °C and 150 rpm for 1 h. The simulated reaction was terminated by adjusting the pH to 7 with 0.1 mL of NaOH solution, and the microstructure of the emulsion droplets digested with simulated gastric fluid was photographed. When simulating intestinal digestion, the emulsion digested with SGF was mixed with SIF at a ratio of 1:1 (v / v), and the pH was adjusted to 7 again. The resulting mixture was incubated at 37 °C and 150 rpm for 2 h, maintaining the pH at 7. The final morphology of the emulsion droplets after gastrointestinal digestion was photographed. Finally, the remaining EO in the emulsion was calculated by simulating intestinal digestion using a UV-visible spectrophotometer. The bioaccessibility of EO in the emulsion was calculated as follows: Bioavailability (%) = (Concentration after EO digestion) / (Concentration before EO digestion) * 100 Table 2: Bioaccessibility of CNC2 / Ca-PE and CNC-PE after simulated gastrointestinal digestion in Example 4, Example 2 and Example 5

[0080] The results were analyzed by Fig.25 and Fig.26 It can be seen that compared with the freshly prepared CNC-PE in Comparative Example 1, the emulsion droplets after gastric acid digestion are severely aggregated due to structural fragmentation. This is because the adsorption capacity of CNC at the interface is limited and the balance of electrostatic interaction in the system is broken, and the CNC-PE droplets aggregate during the gastric digestion stage. The CNC / Ca-PE droplets aggregate in the gastric phase, where the dissolution of the CaCO3 particles destroys the integrity of the shell protecting the oil droplets. The CaCO3 obtained by acid hydrolysis 2+ It provides calcium for the biological processes of the human body 2+ An effective method. Fig. 27 It can be seen that the number of CNC-PE and CNC / Ca-PE emulsion droplets decreased significantly in the intestinal stage, because the intestinal fluid diluted the emulsion again, accelerating the secondary destruction of the droplets destroyed in the gastric stage. In addition, the bile salt ions and lipase in the simulated intestinal fluid competed with the nanocomposite particles at the oil-water interface, resulting in the removal of the nanocomposite particles from the oil-water interface.

[0081] From Table 2 and Fig.28 It can be seen that the bioaccessibility of CNC-PE, CNC2 / Ca1-PE, CNC2 / Ca2-PE and CNC2 / Ca3-PE was 74.83±0.89%, 48.85±4.82%, 59.11±4.44% and 36.06±0.97%, respectively. Compared with CNC2 / Ca1-PE, CNC2 / Ca2-PE and CNC2 / Ca3-PE, CNC-PE has a high bioavailability, indicating that CNC-PE can better protect EO from gastrointestinal degradation, which may be related to its stability in the gastrointestinal tract. The low bioaccessibility of CNC / Ca-PE indicates that most of EO is rapidly absorbed or metabolized in the gastrointestinal stage. In summary, this study demonstrated that CNC / Ca-PE has better long-term stability and acid-responsive release, and is a reliable gastrointestinal targeted release formulation.

[0082] Test Example 10: Antibacterial Activity The antibacterial activity of the emulsion was investigated by the disc diffusion method. The antibacterial activities of CNC / Ca-PE, CNC-PE and CaCO3-PE in Examples 1 to 5 were evaluated using Gram-positive bacteria (Staphylococcus aureus) and Gram-negative bacteria (Escherichia coli). After separation, a single colony was selected and inoculated into liquid sterile LB medium for incubation. Carefully and evenly spread 0.2 mL of bacterial solution (about 106 CFU / mL) on a sterile solid culture medium and incubated at 37 °C for 0.5 h. Sterile drug-susceptible sheets (6 mm) loaded with 40 μL of emulsion and 10 μL of levofloxacin (25 μg / mL) were placed on the culture medium, incubated at 37 °C for 24 h, and the inhibition zone was determined. Each experimental group included 1 levofloxacin group and 3 emulsion sample groups, see Fig.29 , Fig.30 and Table 3.

[0083] Table 3: Encapsulation efficiency of CNC / Ca-PE and CNC-PE in Examples 1 to 5 and inhibition zones against Escherichia coli and Staphylococcus aureus

[0084] according to Fig.29 , Fig.30As shown in Table 3, in Comparative Example 1, CNC-PE showed a smaller inhibition zone, indicating that the growth of Escherichia coli and Staphylococcus aureus was inhibited to a certain extent. In Comparative Example 2, CaCO3-PE had no obvious effect on the growth of Escherichia coli and Staphylococcus aureus, and only encapsulated a small amount of EO. The size of the inhibition zone of emulsions stabilized by CNC / Ca at different ratios is related to their viscosity, EE and release rate. CNC2 / Ca1-PE, CNC2 / Ca2-PE and CNC3 / Ca2-PE have larger inhibition zones for Escherichia coli and Staphylococcus aureus, mainly due to the higher EO encapsulation amount, which is consistent with the results of EE. In addition, the change in the inhibition zone may be related to the interaction between the nanocomposite and EO. According to the CNC / Ca-PE cryo-SEM images, the network structure between the CNC2 / Ca1-PE and CNC2 / Ca2-PE droplets causes the release path of the EO antibacterial active ingredients to be more tortuous. While CNC2 / Ca1-PE and CNC2 / Ca2-PE have higher EE, gradually releasing more EO and forming obvious inhibition zones. In addition, the EO-loaded emulsion has a stronger inhibitory effect on the growth of E. coli than on S. aureus, which may be due to the additional hydrophobicity of the outer membrane to E. coli, while E. coli has a better affinity for carvacrol. The inhibitory effect of the CNC-loaded EO emulsion on E. coli is stronger than that on S. aureus. The cell wall of S. aureus may be denser, thus hindering the penetration of EO components. The inhibition zones of CNC2 / Ca1-PE and CNC2 / Ca2-PE on S. aureus are larger than those on E. coli, and the inhibition effect on S. aureus is stronger. This is due to a certain concentration of Ca 2+ It rapidly destroyed the phospholipid vesicles of the cell membrane of Staphylococcus aureus but failed to affect Escherichia coli. 2+ The CNC2 / Ca3-PE with the highest relative concentration did not show an inhibition zone. This may be due to the special structure of the CNC2 / Ca3 complex, and the encapsulation of CNC on CaCO3 particles prevented the Ca 2+ Contact with bacterial cell membrane.

[0085] The design focus of the present invention is that CNC / Ca nanocomposite particles with different mass ratios were successfully prepared in this study; CNC affects the growth and shape of CaCO3 grains through electrostatic action and complexation, thereby producing nanoscale composite particles as PE stabilizers. Compared with CNC-PE and CaCO3-PE, CNC / Ca-PE has excellent stability. In addition, except for CNC1 / Ca2-PE and CNC2 / Ca3-PE, all CNC / Ca-PE remain stable for up to 4 months. Due to the participation of CaCO3 in the system, CNC / Ca-PE exhibits pH-responsive behavior, which is manifested as an increase in the emulsion particle size, destruction of the shell and three-dimensional structure, and rapid release in acidic media. EO-loaded CNC / Ca-PE nanocomposite particles show good antibacterial activity, and their emulsification properties and structure affect the antibacterial activity of the composite particles. CNC / Ca-PE has a high drug loading capacity and is expected to become a pH-responsive oral drug carrier.

[0086] The above description is only a preferred embodiment of the present invention and does not limit the technical scope of the present invention. Therefore, any slight modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention are still within the scope of the technical solution of the present invention.

Claims

1. A method for preparing an acid-responsive emulsion, characterized in that: The steps include: S1, preparing volatile oil; S2. preparing a CNC suspension: dispersing microcrystalline cellulose in sulfuric acid, stirring in a water bath, and then terminating the reaction; centrifuging the reaction product to separate the precipitate; dialyzing the reaction product to displace excess sulfuric acid to obtain a CNC suspension with a constant pH; S3, preparation of CNC-CaCO3 composite particles: put Ca(OH)2 into pure water, stir at room temperature to obtain Ca(OH)2 solution; add CNC suspension, stir at room temperature to make the two mixed evenly; then introduce CO2 gas at a uniform flow rate, stir at room temperature to obtain CNC-CaCO3 composite particles; S4. Preparation of composite emulsion: using volatile oil as oil phase and CNC-CaCO3 composite particles as water phase, dropping the oil phase into the water phase containing CNC-CaCO3 composite particles, shearing, homogenizing, and obtaining a composite emulsion.

2. The method for preparing an acid-responsive emulsion according to claim 1, characterized in that: In the S2, microcrystalline cellulose is dispersed in 20 times the mass fraction of 64% sulfuric acid, stirred in a water bath at 45°C and 400 rpm for 45 min, and then 10 times the mass fraction of pure water is added to terminate the reaction; the reaction product is centrifuged at 4°C and 5000 rpm for 10 min to separate the precipitate.

3. The method for preparing an acid-responsive emulsion according to claim 1, characterized in that: In S2, the reaction product is encapsulated in a regenerated cellulose dialysis bag and dialyzed to replace excess sulfuric acid. The CNC suspension with a constant pH is obtained by dialyzing for 5 days.

4. The method for preparing an acid-responsive emulsion according to claim 1, characterized in that: In S3, Ca(OH)2 is placed in pure water, and stirred at room temperature using a magnetic stirrer at 500 rpm for 10 min to obtain a Ca(OH)2 solution with a mass fraction of 0.07%-0.14%.

5. The method for preparing an acid-responsive emulsion according to claim 1, characterized in that: The CNC suspension was added to the S3, and stirred at 500 rpm with a magnetic stirrer for 10 min at room temperature to make the two mixed evenly; then CO2 gas was introduced at a uniform flow rate for 10 min, and stirred at 500 rpm with a magnetic stirrer for 10-12 h at room temperature to obtain CNC-CaCO3 composite particles.

6. The method for preparing an acid-responsive emulsion according to claim 1, characterized in that: The volatile oil in S4 includes tea oil and Elsholtzia jiangruta volatile oil. The specific preparation process of the Elsholtzia jiangruta volatile oil is as follows: weigh Elsholtzia jiangruta medicinal materials, add 6-8 times of water, distill and extract for 3-5 hours, separate the water layer and the volatile oil layer, add anhydrous sodium sulfate to the volatile oil layer for dehydration, and obtain Elsholtzia jiangruta volatile oil.

7. The method for preparing an acid-responsive emulsion according to claim 1, characterized in that: The S4 was sheared at 22000 rpm for 5-10 min.

8. The method for preparing an acid-responsive emulsion according to claim 1, characterized in that: The homogenization conditions in S4 are: homogenization in a high-pressure homogenizer at a pressure of 300 bar and 500 bar for 10-30 min respectively.

9. The method for preparing an acid-responsive emulsion according to claim 1, characterized in that: The CNC-CaCO3 composite particles in S3 include CNC / Ca2 composite particles and CNC2 / Ca composite particles.

10. The method for preparing an acid-responsive emulsion according to claim 1, characterized in that: The composite emulsion in S4 includes CNC / Ca2 composite emulsion and CNC2 / Ca composite emulsion.

Citation Information

Patent Citations

  • Preparation method of high-internal-phase emulsion with stable cellulose nano-crystals

    CN108530649A

  • Pickering emulsion stabilized by nanocellulose hydrogel

    CN113501973A

  • Preparation method of hairy nanocrystalline cellulose Pickering emulsion

    CN114539557A

  • Corn protein-silicon dioxide compound emulsion as well as preparation method and application thereof

    CN114702832A

  • Low-oil-phase Pickering emulsion with stable nanocellulose-chitosan nanoparticles and preparation method of low-oil-phase Pickering emulsion

    CN117603465A